Tunable actuation behavior of ionic polymer metal composite utilizing carboxylated carbon nanotube-doped Nafion matrix. Issue 6 (15th January 2018) - Ru, Jie; Zhu, Zicai; Wang, Yanjie; Chen, Hualing; Li, Dichen
Abstract : In this study, we propose to neutralize the relaxation deformation of Nafion-ionic polymer metal composite (IPMC) by slow anode deformation of Flemion-IPMC caused by carboxyl groups (–COOH). Abstract : In this study, we propose to neutralize the relaxation deformation of Nafion-ionic polymer metal composite (IPMC) by slow anode deformation of Flemion-IPMC caused by carboxyl groups (–COOH). Carboxylated carbon nanotubes (CCNT) as –COOH carriers were doped into a Nafion matrix. By adjusting the doping content from 0 wt% to 10 wt%, an IPMC with constant steady-state deformation has been achieved at a critical CCNT content of 2 wt%. Moreover, the increasing rate of the slow anode deformation with the CCNT content is tunable, which is found to be 2.26 mm s −1 % −1 .